The Effects of Prize Spread and Noise in Elimination Tournaments: A Natural Field Experiment - Josse Delfgaauw; Robert Dur; Arjan Non; Willem Verbeke (Tinbergen Institute, 2011)
We conduct a field experiment in a large retail chain to test basic predictions of tournament theory regarding prize spread and noise. A random subset of the 208 stores participates in two-stage elimination tournaments. Tournaments differ in the distribution of prize money across winners of the first and second round of the tournament. As predicted by theory, we find that a more convex prize spread increases performance in the second round at the expense of first-round performance, although the magnitude of these effects is small. Moreover, the treatment effect is significantly larger for stores that historically have relatively stable performance as compared to stores with more noisy performance.
urn:NBN:nl:ui:15-1765/25711
Keywords: C93; M51; M52; 330; Elimination tournaments; Incentives; Prize spread; Performance measurement; Field experiment; Extensives Spiel; Handelskette; Filiale; Wettbewerb; Feldforschung; Niederlande